The Use of Recreational Fishers’ Ecological Knowledge to Assess the Conservation Status of Marine Ecosystems - Pita, Pablo; Antelo, Manel; Hyder, Kieran; Vingada, José; Villasante, Sebastián (Frontiers in Marine Science, 2020)
Fisheries scientists and marine resource managers are reluctant to incorporate Fishers’ Ecological Knowledge (FEK) into technical advice procedures to guide management decisions on marine ecosystems and fisheries. However, in data-poor scenarios FEK has proved to be useful to provide alternative references of biological changes. Moreover, despite recreational fishers are the main potential source of FEK, they have been scarcely incorporated in scientific investigations. In this study it has been evaluated for the first time the use of recreational FEK to assess the conservation status of marine ecosystems in Galicia (NW Spain), a region characterized by a highly complex marine socioecological system integrated by a worldwide commercial fleet and a powerful recreational sector, among other relevant stakeholders. Active spear fishers and anglers were recruited to provide their perceptions on the conservation status of fish stocks and on the impacts on marine ecosystems. The audio of face to face interviews were transcribed into text and analyzed by using text mining tools. Acknowledged key concepts were used to quantify fishers’ perceptions on changes in the conservation status of their target fish stocks and to identify and quantify the main impacts on marine ecosystems. Overfishing and habitat loss, followed by biodiversity impoverishment, pollution and ocean warming were blamed by the fishers as the main responsible of poor status of conservation of cephalopods and finfish stocks targeted by both commercial and recreational fisheries. Perceived temporal declines in fish stocks were consistent with available biological data, validating the use of recreational FEK to assess long-term ecological changes in the absence of ordinary scientific data. FEK researchers are encouraged to include inputs of different resource users, including fishers following familiar traditions in commercial and/or recreational fisheries because they were more sensible to detect impacts on natural and cultural community heritage. Conservation status of ballan wrasse Labrus bergylta and kelp beds are especially worrying due to their role as key species in coastal ecosystems. The creation of monitoring programs to assess the status of this fish and other commercially and/or recreationally relevant species, including kelps, are urgently needed to ensure the future conservation of marine ecosystems.